The effect of complete denture wearing on food preference and nutrition of patients in the Prosthodontic Section of the UP Manila College of Dentistry - Delos Reyes, Joanne RJ G.
Introduction: This study aims to determine the effect of complete denture wearing on food preference and nutrition of edentulous patients in the Prosthodontic Section of the UP Manila College of Dentistry.